The challenge of learning to read written English for the profoundly pre-lingually deaf adult - Furlonger, Brett Edward (Penerbit Universiti Kebangsaan Malaysia, 2016)
Many adults with profound prelingual deafness have difficulties reading and comprehending written English and this problem may originate from English phonological deficits and/or difficulties connecting sign language with written English. The purpose of this study was, therefore, to investigate the word coding strategies of profoundly deaf adults with a view to identify to what extent they used speech-based and sign-based strategies to process English text. For the gathering of the data participants completed three tasks: (1) a measure examining the use of speech and sign-based word coding during reading (2) a phoneme awareness task (3) and a task assessing skill in applying grapheme-phoneme correspondences. Data was analysed using tests of difference (t-tests and ANOVA) with the findings showing that while the less proficient readers had significantly greater English phonological deficits they reported only a minimal use of supplementary sign language coding strategies. Surprisingly, some of the proficient readers, with good English phonological skills chose to supplement them with some sign-based strategies. The possible reasons and instructional implications for these findings are discussed.